Mediation analysis - Iacobucci, Dawn. (Quantitative applications in the social sciences ;, 2008)
This text explores even the fundamental assumptions underlying mediation analysis and describes options for analyzing mediation data as well as providing syntax for a widely available and popular computer program so users can begin implementing mediation ideas immediately on their data.